OPTIMIZATION OF THE NUMBER OF AVSEC PERSONNEL EXPECTS TO IMPROVE PERFORMANCE AT SECURITY CHECK POINT 1 (SCP 1) SULTAN THAHA JAMBI AIRPORT - Dwi Oktavianingrum, Errica; Musadek, Ahmad; Silk Moonlight, Lady (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Sultan Thaha Airport is an domestic airport located in Jambi City,Jambi Province managed by PT. Angkasa Pura II. Sultan Thaha Airport has a flight schedule of around 9-12 flights every day which is quite crowded with passengers. If you look at the high movement of passengers at Sultan Thaha Airport, it can be fatal if an accident occurs. Therefore, the implementation of Aviation Security checks at Security Check Point (SCP)s must be further tightened supported by the availability of facilities and procedures in accordance with existing regulations.This study aims to determine satisfaction with the level of service provided to Security Check Point (SCP) (SCP) I officers in accordance with This study aims to ascertain whether the efforts made have fully met the standards in maintaining flight operational safety areas with flight activities at Sultan Thaha Airport in accordance with the Decree of the Minister of Transportation No KM 211 of 2020 concerning National Aviation Security.The method used in this study is qualitative descriptive which refers to the Decree of the Minister of Transportation No KM 211 of 2020 concerning National Aviation Security Order and Airport Services Manual (ICAO) doc. 9137 Part 6. Control Of Obstacles. Information collection procedures include observation, interviews, and literature studies. Airports related to services provided by Aviation Security officers can be improved optimization of existing facilities and procedures to avoid dangers to flight security and safety at Sultan Thaha Airport.